Diseño y diagramación de un libro ilustrado para la difusión de cuentos y leyendas originarios del pueblo de Zumbahua en los idiomas kichwa y español dirigido a los niños y niñas de educación básica de la Unidad Educativa Comunitaria Intercultural Bilingüe (UECIB) “24 de octubre” de la comunidad la Cocha-Zumbahua-Pujilí-Cotopaxi - Chaluisa Pallo, Wilson Gustavo (2016)
In all regions of the Republic of Ecuador mission, it is to ensure state intercultural education for all and all children, youth and citizens at all levels and types of education, and cultural relevance for communities, peoples and nationalities. An important step is to strengthen cultural ancestral tales and legends through as a visual resource that allows to extend the scope to other artistic and cultural expressions, which is the main facilitator for the elaboration of an illustrated book that will offer educational units in the province of Cotopaxi, it represents the cultural and unique identity of the people of Zumbahua, revaluing and promoting cultural values through stories and legends, providing advice by the moral and use of content and meaning from the native peoples of ancient characters and creative cultures and La Cocha community.